1986
DOI: 10.1017/s0014479700014599
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the proportion of Species on the Yield and Quality of Forage Mixtures, and on the Yield of Barley in the Following Year

Abstract: S U M M A R YMixtures of legumes and cereals in various proportions (seed ratios) were evaluated in Northern Syria for forage production and quality and for yield of barley grain in the following year. Both a vetch-cereal and pea-cereal mix were tested in proportions of 0:100, 33:66, 50:50, 66:33 and 100:0. The study was carried out between 1982 and 1985, covering two seasons for forage production and two for grain production. Dry matter yields of the mixtures exceeded the yield of either one or both component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
2

Year Published

1988
1988
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 10 publications
(9 reference statements)
6
32
2
Order By: Relevance
“…Salehi et al (2016) reported that the highest seed yield of fenugreek and buckwheat was found with fenugreek: buckwheat (2:1) intercropped with organic manure. Similar to our results, Osman and Nersoyan (1986) found that the highest dry matter yields in cereal-common vetch intercrops for forage production were related to a high share of the legume partner. A higher AGDM at the flowering stage and higher seed yields with both IF and BL compared with mineral fertilizer could be the result of several factors, such as the effect of broiler litter supplying more nutrients over the growing season for plant growth and seed filling.…”
Section: Discussionsupporting
confidence: 91%
“…Salehi et al (2016) reported that the highest seed yield of fenugreek and buckwheat was found with fenugreek: buckwheat (2:1) intercropped with organic manure. Similar to our results, Osman and Nersoyan (1986) found that the highest dry matter yields in cereal-common vetch intercrops for forage production were related to a high share of the legume partner. A higher AGDM at the flowering stage and higher seed yields with both IF and BL compared with mineral fertilizer could be the result of several factors, such as the effect of broiler litter supplying more nutrients over the growing season for plant growth and seed filling.…”
Section: Discussionsupporting
confidence: 91%
“…Comparable results were found by Assefa and Ledin (2001) and Tuna and Orak (2007), who used the same oat: vetch ratio. Nevertheless, in the second year of the experiment, despite the lower oat:vetch ratio the oat-vetch mixture outyielded the monocrop of oat, which contradicts most other studies (Droushiotis 1989;Caballero, Goicoechea, et al 1995;Lithourgidis et al 2006) where oat monocultures had a significant advantage over oat-vetch mixtures, but agrees with Osman and Nersoyan (1986). In 2006, mineral fertilizer gave 8.7% higher forage yield than the organic fertilizer, while in 2007, organic fertilizer resulted in a yield that was 9% higher than that of mineral fertilizer, although no significant differences were detected.…”
Section: Discussioncontrasting
confidence: 79%
“…Forage yield and quality of mixtures depends on the species composition and/or proportion and the phenology at harvesting time (Droushiotis 1985;Roberts et al 1989). Overyielding in mixtures of cereals and legumes may occur when competition between species is lower than between members of the same species (Osman and Nersoyan 1986;Caballero, Goicoechea, et al 1995). Both yield and quality determine the number of livestock a specific crop can support, that is, its carrying capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, grasses and legumes are considered as important forage crops because of their nutritional value, especially protein content in legumes and crude fiber in grasses (Rakeih et al, 2008). However, monocultures of legumes or grasses do not provide satisfactory results for forage production and nutritive value (Osman and Nersoyan, 1986). Thus, mixing legume forages with grass forages can be an effective way to improve forage quality and nutritive value of the end product (Ross et al, 2004;Lithourgidis et al, 2006).…”
Section: Introductionmentioning
confidence: 99%